2023
DOI: 10.3390/md21030180
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Degradation of Alginate and Preparation of Alginate Oligosaccharides by a Novel Biofunctional Alginate Lyase with High Activity and Excellent Thermophilic Features

Abstract: The enzymatic degradation of seaweed polysaccharides is gaining interest for its potential in the production of functional oligosaccharides and fermentable sugars. Herein, a novel alginate lyase, AlyRm3, was cloned from a marine strain, Rhodothermus marinus DSM 4252. The AlyRm3 showed optimal activity (37,315.08 U/mg) at 70 °C and pH 8.0, with the sodium alginate used as a substrate. Noticeably, AlyRm3 was stable at 65 °C and also exhibited 30% of maximal activity at 90 °C. These results indicated that AlyRm3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It has been reported that the active site of FsAlgB is located within two flexible loops, and that both polyG and polyM in the substrate molecules could bind to the active site . Furthermore, structural analysis of the bifunctional alginate lyase, AlyRm3, revealed that the complex substrate ΔMG can bind to a long cleft formed between the N-terminal domain and central domain . To the best of our knowledge, this study is the first to explore different binding sites in a bifunctional alginate lyase for different substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the active site of FsAlgB is located within two flexible loops, and that both polyG and polyM in the substrate molecules could bind to the active site . Furthermore, structural analysis of the bifunctional alginate lyase, AlyRm3, revealed that the complex substrate ΔMG can bind to a long cleft formed between the N-terminal domain and central domain . To the best of our knowledge, this study is the first to explore different binding sites in a bifunctional alginate lyase for different substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Understanding the detailed mechanisms of bifunctional enzymes will help to optimize protein engineering applications and elucidate how enzymes might have evolved . In recent years, the structure and substrate-binding sites of several bifunctional alginate lyases have been predicted, such as AlyPL17, AlyRm3, and FsAlgB . However, there has been no mutation verification work so far, and this is the first time mutation verification was conducted based on docking results.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation